Pemanfaatan Teknologi Gawai pada Pembelajaran Anak SD di Era Pandemi Covid-19 dengan Menggunakan Metode Project Based Learning - Amana Wahyu Sulaiman; Mardiana Saputri (UM Purwokerto Press, 2021)
Learning in the current era of the COVID-19 pandemic is carried out online, using screen-to-screen which is difficult in the teaching and learning process, both teachers and students in general. Learning using gadgets or gadgets that must be used by students. In this case, sometimes elementary school students actually abuse the use of technology that is outside the function of the student learning process. Student learning time is only 1-2 hours, they face the screen using a device. After that the children actually use these devices to play online games, play YouTube, play social media and others, which have an impact on the decreasing quality of children's learning. So from this there must be motivation to learn in improving learning in elementary school children. In general, elementary school children are not allowed to use devices, because their age is still vulnerable. Through this, that children must be closely monitored and they must really make the best use of their devices, so that later children can learn optimally through learning stages or learning projects. This learning project requires tiered learning which has a function as a form of student activity while at home in the current pandemic era. This learning project is intended for thematic learning, so that there are several lessons that will be made learning projects that can maximize learning in children.